Physical Forcing Controls the Basin‐Scale Occurrence of Nitrogen‐Fixing Organisms in the North Pacific Ocean. Issue 9 (16th September 2020) - Cheung, Shunyan; Nitanai, Risa; Tsurumoto, Chihiro; Endo, Hisashi; Nakaoka, Shin‐ichiro; Cheah, Wee; Lorda, Jaime Färber; Xia, Xiaomin; Liu, Hongbin; Suzuki, Koji
Abstract: Biological nitrogen fixation is increasingly recognized as an important source of new nitrogen in a warming ocean. However, the basin‐scale spatiotemporal distribution of nitrogen‐fixing organisms (diazotrophs) in the ocean and its controlling environmental factors remain unclear. Here we examined the basin‐scale seasonal distribution patterns of major diazotrophs (filamentous cyanobacterial Trichodesmium, unicellular cyanobacterial UCYN‐A1, and proteobacterial Gamma‐A) in surface waters of the North Pacific from 2014 to 2016 with unprecedented coverage and resolution. In general, UCYN‐A1, Trichodesmium, and Gamma‐A were abundant during spring‐autumn, summer‐autumn, and spring respectively. Regarding latitudinal patterns of abundance, UCYN‐A1 showed dome shape; Trichodesmium was gradually decreasing from low‐ to high‐latitude regions; and Gamma‐A did not show a clear pattern, which were coincident with the distinct correlations between the diazotrophs and temperature. All three diazotrophs were abundant (reached 10 6 –10 7 nifH gene copy number L −1 ) in the North Pacific transition zone and subtropical gyre, where the cyanobacterial diazotrophs were more abundant in both the western and eastern North Pacific than in the central North Pacific. The diazotroph abundance in the western North Pacific was positively correlated with eddy kinetic energy and sea surface height anomaly, which implies an enhancement of diazotrophs in mesoscale eddies associated with the western boundary current Kuroshio and its extension. The cyanobacterial diazotrophs were positively correlated with wind stress curl, a measurable parameter of wind‐driven upwelling, in the eastern North Pacific. Our study refines the biogeography of three major diazotrophs and highlights the importance of physical forcing in mediating their dynamics. Key Points: Diazotrophs showed seasonal succession and different longitudinal patterns, which were explained with their different temperature preference Abundant diazotrophs were detected in the North Pacific transition zone in both western and eastern North Pacific Diazotrophs in western and eastern North Pacific were correlated with proxies of mesoscale eddies and coastal upwelling, respectively